EMBRYONIC DEVELOPMENTAL STAGES OF AFRICAN GIANT CATFISH Heterobranchus longifilis (Valenciennes, 1840) (TELEOSTEI, CLARIIDAE) - Wilfred-Ekpripo, P.C; Okunade, O. A.; Akintayo, I. A.; Akanmu, O. A.; Ihimekpen, F. A.; Afolabi, E. S.; Ejiogu, I. N.; Anyanwu, P. E.; Ayaobu-Cookey, I. K.; Okiria, E.; A. O. Ogbolu, A. O. Ogbolu (Nigerian Journal of Fisheries, 2018)
The embryonic developmental stages in Heterobranchus longifilis were assessed. Matured specimens of male (1.9kg) and gravid female (2.3kg) broodstock of H. longifilis were selected. The female broodstock was injected with 1.1ml ovaprim and stripped after the latency period of 11 hours. The ovulated eggs collected were fertilized with the male milt. Fifty five fertilized eggs were distributed randomly into each of labeled 13 transparent plastic bowls, filled with 50 ml of freshwater. Hatchability rate and egg developmental stages were examine simultaneously every two hours with microscope. The first cleavage cell division occurred 30 minutes after the fertilization of eggs while the morula stage was observed within 2 hours. The blastula stage occurred between 2 and 8 hours, while the gastrula stage was 12 and 18 hours. Thereafter, neurulation period and embryonic body formation appeared. The optical vesicle and auditory vesicle formed. Finally, muscular contraction, tail formation, heartbeat, and hatching occurred. The young larva emerged from the embryonic membrane at 24.46 hours with vigorous lashing of the caudal region against the chorion membrane. The average weight and length of the yolk larvae were 0.005g and 0.43 cm respectively. The percentage of fertilization and hatchability rates was 82.50 and 65.10% respectively.